Efficient Synthesis of a Wide‐Range Absorbing Azaphthalocyanine Dark Quencher and Its Application to Dual‐Labeled Oligonucleotide Probes for Quantitative Real‐Time Polymerase Chain Reactions. Issue 38 (7th June 2018) - Demuth, Jiri; Kucera, Radim; Kopecky, Kamil; Havlínová, Zuzana; Libra, Antonín; Novakova, Veronika; Miletin, Miroslav; Zimcik, Petr
Abstract: Unsymmetrical dialkylamino‐substituted zinc azaphthalocyanine (AzaPc) exhibits unique spectral and photophysical properties for dark quenchers of fluorescence in DNA hybridization probes. The panchromatic light absorption of AzaPc from 300 nm up to at least 700 nm and its lack of fluorescence make it an ideal candidate for a universal dark quencher. To prove this experimentally, oligodeoxyribonucleotide probes were labeled at the 3′‐end by this AzaPc and at the 5′‐end by a fluorophore used in the polymerase chain reaction (PCR)—that is, fluorescein, CAL Fluor Red 610, and Cy5. AzaPc showed a significantly higher quenching efficiency compared to the commercially available dark quenchers (BHQ‐1, BHQ‐2, BBQ‐650) in a developed model of TaqMan PCR assay. The AzaPc‐labeled probe proved to also be useful in a practical PCR assay for the quantification of the SLCO2B1 transporter gene expression. The constructed calibration curves indicated linearity in the range from 10 2 to 10 7 of target copies. Abstract : Look to the dark side ! Azaphthalocyanine dark quenchers are able to quench efficiently all routinely used fluorophores in double‐labeled DNA hybridization probes and may be used for quantification of targets in real‐time polymerase chain reactions (see figure).